2019
DOI: 10.26650/eor.2018.478
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of 3D reconstruction technique and Cavalieri’s principle in predicting the mandibular bone defect volumes

Abstract: Comparative assessment of 3D reconstruction technique and Cavalieri's principle in predicting the mandibular bone defect volumes PurposeThe objective of this study was to compare the accuracy of the Cavalieri's principle and 3D reconstruction in predicting the volume of a bony defect. Materials and MethodsDefects of the same approximate size were created on nine artificial mandibles. The actual volume of the defect on each mandible was measured by water displacement, and served as the control. Each mandible wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Since mandibular defects can lead to obvious functional and cosmetic deformities, the repair and reconstruction of mandibular defects has always been a challenge for surgeons ( 9 - 11 ). Reconstruction of mandible with vascularized free bone myocutaneous flap has become the gold standard for reconstruction surgery, which can greatly improve the aesthetic and functional capacity ( 1 , 2 , 12 , 13 ). The main causes of mandibular excision are as follows: squamous cell carcinoma, ameloblastoma, odontogenic keratocyst, osteosarcoma, and ossifying fibroma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since mandibular defects can lead to obvious functional and cosmetic deformities, the repair and reconstruction of mandibular defects has always been a challenge for surgeons ( 9 - 11 ). Reconstruction of mandible with vascularized free bone myocutaneous flap has become the gold standard for reconstruction surgery, which can greatly improve the aesthetic and functional capacity ( 1 , 2 , 12 , 13 ). The main causes of mandibular excision are as follows: squamous cell carcinoma, ameloblastoma, odontogenic keratocyst, osteosarcoma, and ossifying fibroma.…”
Section: Discussionmentioning
confidence: 99%
“…The reconstruction of mandible with vascularized free bone myocutaneous flap has become a standardized procedure for mandibular reconstruction because it can allow a wide range of mandibular defect composite tissue reconstruction. As microsurgery advances, the success rate of vascular anastomosis has neared 100% ( 1 , 2 ). However, we found that there were still some unsatisfactory cases after mandibular reconstruction.…”
Section: Introductionmentioning
confidence: 99%